Poor Sleep Quality of Hospitalized Geriatric Patients in General Hospital in Karawaci, Tangerang, Banten Province, Indonesia - Nata Pratama Hardjo Lugito; Theo Audi Yanto; Andree Kurniawan; Indra Wijaya; Margaret Merlyn Tjiang; Resa Setiadinata; Stevent Sumantri; Euphemia Seto (Medicinus, 2018)
Background: In Indonesia, geriatric population in the year 2005 was 15.8 million (7.2 % population), and expected to reach 11.34% in the year 2020. There was growing evidence for poor sleep as an independent risk factor for poor physical and mental health. Geriatric population may be particularly vulnerable to effects of sleep disturbance due to significant age-related changes in both sleep and inflammatory regulationObjective: To study the epidemiological (gender, age group) and health status (co-morbidities), sleep quality according to Pittsburgh Sleep Quality Index (PSQI) and its associations in geriatric population hospitalized in General Hospital in Karawaci, Tangerang, Banten Province, Indonesia.Materials and Methods: A hospital based cross sectional study was conducted from January to June 2014. A total of 92 subjects aged 60 years and above were selected consecutively from hospitalized geriatric patients for this study. The data was analyzed by means and proportions.Results: The male and female subjects were 51.1% and 48.9%. Mean age was 66.79 + 5.448 years. The age group of 60 – 75 years and above 75 years was 92.4% and 7.6% consecutively. Subjects with diabetes, hypertension, allergy, asthma, cardiac failure and chronic kidney disease were 30.4%, 62.0%, 18.5%, 21.7%, 21.7%, 20.7% consecutively and 63.0% with more than 2 co-morbidities. According to PSQI 72.8% subjects have poor sleep quality. Associations between poor sleep quality to epidemiological and health status were not significant except for diabetes (RR= 3.208 [95% CI: 1.045 – 9.848], p = 0.022) and chronic kidney disease (RR= 6.247 [95% CI: 0.902 – 43.279], p = 0.017)Conclusions: Seventy two percents of subjects have poor sleep quality, and associations between poor sleep quality to epidemiological and health status were not significant except for diabetes.